INVESTIGATING THE IMPACT OF INTERVENTIONS USING CONCRETE AND VIRTUAL MANIPULATIVES ON 3 TH GRADE STUDENTS’ FRACTION CONCEPT AND MOTIVATION: - Ukdem, Serife; Cetin, Hatice (International Online Journal of Education and Teaching, 2022)
The purpose of this study is to examine the effect of using concrete and virtual manipulatives relevant fraction subject to 3rd grade students’ understanding of fractions and motivation towards mathematics lesson. The study group consists of 61 students studying in three different classes at the 3rd grade level of a private primary school in Turkey. Quantitative research method, pretest and posttest, and a quasi-experimental research design including two experimental and one control group was adopted. The study was carried out by the experimental-1 group with concrete manipulative-assisted training, the experiment-2 group with virtual manipulative-assisted training, and the control group with the traditional teaching in the mathematics curriculum. Data collection tools, the Fraction Comprehension Test (FCT) developed originally with a cronbach alpha reliability coefficient of 0.874 and the Mathematics Lesson Motivation Scale (MLMS) for primary schools was used. One-way MANOVA was used for analysing the data. As far as the research findings; using manipulatives makes a statistically significant difference in the understanding of fractions of 3rd grade students (F(2-60) = 9.171, p<.05), but it was detected that there was not statistically important difference (F(2-60)= 0.163, p>.05) in motivation for mathematics lessons. It is seen that 24% of the change in comprehension is caused by using manipulative. Concrete manipulative using and virtual manipulative using have no superiority in terms of both fraction comprehension and mathematics motivation when compared to each other. It can be suggested that using manipulatives as complementary to each other may give better results.